Pola Konsumsi Perempuan Kuli Panggul di Pasar Sayur Magetan - Kinanthi Damayanti; Ninik Srijani; Novita Erliana Sari (Universitas PGRI Madiun, 2021)
This study aims to determine the consumption patterns of female porters in the Magetan vegetable market. The type of research used is qualitative research through a case study approach. The total number of informants is 40 people. Collecting data through observation, interviews, documentation. The validity of the data using triangulation. The data analysis technique uses data reduction, data presentation and verification. The results showed that, (1) Due to the high economic needs, and low income, the women chose to become porters, they chose this job because there was no other job. (2) There is not much income per day as porters, they work from morning at 07.00-15.00 WIB, they earn around Rp. 50,000-Rp. 70,000. (3) Before becoming porters, among them were only household workers, fried food sellers, farm laborers, where they rarely had buyers. (4) Obstacles that are often experienced by female porters are decreased health factors, bone pain, sometimes colds, dizziness. In addition, there is another factor, namely the quiet market conditions. (5) With a mediocre and uncertain income, female porters always prioritize basic needs, namely clothing, food, and housing. However, if they have more money, they will choose to save it, just in case there is an urgent need. (6) From the interviews, according to them the needs that have been fulfilled, namely household needs including kitchen needs, electricity bills, PDAM water bills, children's school bills, and basic needs can be met every day